The Role of Sub-District Headmen in Examining Policies of Local Government Organizations Mueang Buriram District Buriram Province - Jongmeesuk , Thanapat; Phromsathit, Sakon; Tosamas, Pattarapol; Wichairam, Sathaphon (Interdisciplinary Academic and Research Journal, 2023)
The roles and duties of sub-district chiefs and village headmen are by the framework of the law defined as local rulers according to the mechanisms of provincial administration and representing the government sector closest to the people. The powers and duties of the village headman at present, the village headman and the village headman play an important role in the administration of the country, as both of them are likened to the limbs or coordinators between the state and the people. This research aims to (1) study the level of participation in policy auditing; (2) study the participation in policy auditing components at the local level; (3) to analyze the confirmatory components of village headmen and village headmen (5) to study policy recommendations of sub-district chiefs and village headmen on their participation in policy auditing at the local level This study was conducted with population groups, namely village headman, village headman, inspector, village headman, assistant village headman. in the area of Mueang Buriram District Buriram Province The sample group consisted of 291 people. The sample group was determined by Taro Yamane's sampling formula. The level of participation in the policy examination of sub-district headmen, and village headmen, and statistics used in the analysis were frequency, mean, percentage, division, standard deviation, and parameter estimation. Consistency of the hypothetical correlation model with the data manifested by the chi-squared statistic. The findings showed that; (1) The role level of participation in policy auditing was found that the overall picture was high. (2) Policy Audit Participation Elements It was found that the KMO value was 0.755, suitable for elemental analysis. Pearson's correlation coefficient Passed the criterion with discriminant power ranging from 0.208 to 0.889, it was suitable for elemental analysis. (3) Confirmatory component analysis found that There are 8 factors affecting 30 indicators. (4) Analyzing factors affecting policy audit participation, it is found that chi-square (X2) = 2276.252 at degrees of freedom (df) = 977 P- value = 0.051, chi-square relation (X2/df) = 2.32, GFI = 0.984, Adjusted GFI (AGFI) = 0.952, root-square of error by Approximately (RMSEA) = 0.013 and the root of the mean square of the remainder in the form of standardized scores (SRMR). = 0.010.